Environmental Factors Affecting Health Indicators in Sub-Saharan African Countries: Health is Wealth - Zaman, K.; Ahmad, A.; Hamzah, T.A.A.T.; Mariney, M.Y. (Kluwer (now part of Springer), 2016)
Sub-Saharan African countries faced severe environmental hazards that affect the health and wealth of the countries. The study utilized number of environmental factors including carbon dioxide emissions, energy use, fossil fuel energy consumption, land used under cereal production, household final consumption expenditures and water sanitation facility that have a promising impact on African’s health. The study considered four health variables including external resources for health, health expenditures per capita, life expectancy at birth and out-of-pocket expenditures for seven selected Sub-Saharan African countries namely, Botswana, Cameroon, Kenya, Nigeria, Senegal, South Africa and Sudan for panel data estimations, over the period of 1995–2013. The results confirmed that environmental factors affect the African’s health i.e., carbon dioxide emissions increases the health expenditures per capita, while it decreases the external resource of health in a region. Fossil fuel energy consumption increases the external resources of health and life expectancy while it decreases the out-of-pocket expenditures of the African countries. Life expectancy significantly decreases the external resource of health. Finally, inadequate water sanitation increases the healthcare expenditures while it decreases the external resources of health and life expectancy in Sub-Saharan African countries.